Safety and Efficacy of Intratympanic Alpha-Lipoic Acid Injection in a Mouse Model of Noise-Induced Hearing Loss - Jae Sang Han; Ye Lin Kim; Hyo Jeong Yu; Jung Mee Park; Yeonji Kim; So Young Park; Shi Nae Park (MDPI AG, 2022)
Alpha-lipoic acid (ALA) is an antioxidant with oto-protective effects. In the present study, the safety and effectiveness of ALA therapy after noise-induced hearing loss was confirmed based on the administration method. The safety of intratympanic ALA (IT-ALA) was evaluated with oto-endoscopy and middle ear mucosa morphologic study. Perilymph ALA concentrations according to the administration routes were compared, and the efficacy of ALA was investigated through hearing tests and cochlear histological studies. The middle ear mucosa was swollen 1 week after IT-ALA but completely recovered within 3 weeks. ALA concentration in the perilymph was significantly higher in the IT-ALA group. Recovery of organ of Corti morphology and hearing levels were predominant in the IT-ALA group compared with the intraperitoneal injection group (IP-ALA) and showed similar rescue effects in the IT-dexamethasone group (IT-DEX). Interleukin-1 beta and nuclear factor-kappa B expression was significantly downregulated in the IT-ALA group. IT-ALA showed better cochlear recovery from acoustic trauma with higher inner ear penetration rate than IP-ALA. The rescue effect of IT-ALA after noise-induced hearing loss was similar to IT-DEX; however, the ALA and DEX mechanisms are different. IT-ALA appears to be another safe and effective treatment modality after acoustic trauma and comparable to IT-DEX.